2020
DOI: 10.1136/jim-2020-001592
|View full text |Cite
|
Sign up to set email alerts
|

Gamut of Cardiac Manifestations and Complications of COVID-19: A Contemporary Review

Abstract: COVID-19 has posed an extraordinary burden on health and the economy worldwide. Patients with cardiovascular diseases are more likely to have severe illness due to COVID-19 and are at increased risk for complications and mortality. We performed a narrative literature review to assess the burden of COVID-19 and cardiovascular morbidity and mortality. Myocardial injury has been reported in 20%–30% of patients hospitalized due to COVID-19 and is associated with a worse prognosis and high mortality (~50%–60%). Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…We therefore aimed to address the following research questions: in athletes recovered form SARS-CoV-2 infection: (1) what is the prevalence of SARS-CoV-2 cardiac involvement (as found using imaging investigations), stratified by study quality? ; (2) what is the incidence of ventricular tachyarrhythmia's (and SCA/SCD) in athletes with documented cardiac involvement?…”
Section: Key Messagesmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore aimed to address the following research questions: in athletes recovered form SARS-CoV-2 infection: (1) what is the prevalence of SARS-CoV-2 cardiac involvement (as found using imaging investigations), stratified by study quality? ; (2) what is the incidence of ventricular tachyarrhythmia's (and SCA/SCD) in athletes with documented cardiac involvement?…”
Section: Key Messagesmentioning
confidence: 99%
“…1 Most studies performed early in the pandemic focused on cardiac complications in hospitalised and severely ill patients, but recently, there has been marked interest in SARS-CoV-2 cardiac complications and sequelae in young and healthy individuals, including athletes. 2 The initial studies in asymptomatic athletes or athletes with a mild or moderate course of illness reported considerable sustained cardiac involvement after recovery from SARS-CoV-2 infection. Later studies have not replicated these findings.…”
Section: Introductionmentioning
confidence: 99%
“…The final result may also be a product of the both processes when direct viral entry and replication in myocardium may enhance the susceptibility to myocardial injury, which then leads to myocarditis as a part of inflammatory response. Right ventricular dysfunction can also result from the strain caused by increased pulmonary vascular resistance and the workload on the right heart [3]. HF in COVID-19 patients is usually acute and represents de novo cases rather than exacerbation of previously diagnosed condition.…”
Section: Introductionmentioning
confidence: 99%
“…Results indicated an ageing-related increase in CD47 expression, which may contribute the increased COVID-19 vulnerability in older patients [Hokello et al, 2020]. Moreover, high CD47 levels are known to be involved in vascular disease, vasoconstriction, and hypertension, which may predispose SARS-CoV-2-infected individuals to various conditions associated with severe COVID-19 related, including pulmonary hypertension, lung fibrosis, myocardial injury, stroke, and acute kidney injury [Soto-Pantoja et al, 2013;Rogers et al, 2017a;Cruz Rodriguez et al, 2020;Fabrizi et al, 2020;Karmouty-Quintana et al, 2020;Scutelnic and Heldner, 2020;Leeming et al, 2021;Sanghvi et al, 2021;Shah et al, 2021].…”
Section: Discussionmentioning
confidence: 99%